Kruppel‐like factor 15 regulates fuel switching between glucose and fatty acids in brown adipocytes. Issue 7 (15th February 2021) - Nabatame, Yuko; Hosooka, Tetsuya; Aoki, Chikako; Hosokawa, Yusei; Imamori, Makoto; Tamori, Yoshikazu; Okamatsu‐Ogura, Yuko; Yoneshiro, Takeshi; Kajimura, Shingo; Saito, Masayuki; Ogawa, Wataru
Abstract: Aims/Introduction: Brown adipose tissue (BAT) utilizes large amounts of fuel for thermogenesis, but the mechanism by which fuel substrates are switched in response to changes in energy status is poorly understood. We have now investigated the role of Kruppel‐like factor 15 (KLF15), a transcription factor expressed at a high level in adipose tissue, in the regulation of fuel utilization in BAT. Materials and Methods: Depletion or overexpression of KLF15 in HB2 differentiated brown adipocytes was achieved by adenoviral infection. Glucose and fatty acid oxidation were measured with radioactive substrates, pyruvate dehydrogenase complex activity was determined with a colorimetric assay, and gene expression was examined by reverse transcription and real‐time polymerase chain reaction analysis. Results: Knockdown of KLF15 in HB2 cells attenuated fatty acid oxidation in association with downregulation of the expression of genes related to this process including Acox1 and Fatp1, whereas it increased glucose oxidation. Expression of the gene for pyruvate dehydrogenase kinase 4 (PDK4), a negative regulator of pyruvate dehydrogenase complex, was increased or decreased by KLF15 overexpression or knockdown, respectively, in HB2 cells, with these changes being accompanied by a respective decrease or increase in pyruvate dehydrogenase complex activity. Chromatin immunoprecipitation showed that Pdk4 is a direct target of KLF15 in HB2 cells. Finally, fasting increased expression of KLf15, Pdk4 and genes involved in fatty acid utilization in BAT of mice, whereas refeeding suppressed Klf15 and Pdk4 expression. Conclusions: Our results implicate KLF15 in the regulation of fuel switching between glucose and fatty acids in response to changes in energy status in BAT. Abstract : Brown adipose tissue (BAT) utilizes large amounts of fuel for thermogenesis with fatty acids and glucose being the major substrates for this process, but the mechanism by which fuel substrates are switched in response to changes in energy status is poorly understood. We here show that KLF15 increases fatty acid oxidation through the regulation of genes related to fatty acid utilization, whereas this transcription factor inhibits glucose oxidation via direct up‐regulation of PDK4 expression and attenuation of PDC activity, in HB2 differentiated brown adipocytes. Given that KLF15 expression in BAT was up‐regulated in response to fasting and down‐regulated after subsequent refeeding in mice and that these changes were accompanied by alterations in the expression of genes related to glucose and lipid utilization, KLF15 might play an important role in the regulation of fuel switching between glucose and fatty acids in response to changes in energy status in BAT.